The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1037/vio0000268
|View full text |Cite
|
Sign up to set email alerts
|

Measuring teen dating violence perpetration: A comparison of cumulative and single assessment procedures.

Abstract: Objective: There are concerns about the measurement of teen dating violence (TDV) perpetration. The current study compares data on TDV perpetration derived from a cumulative assessment procedure and a single assessment procedure. The prevalence and frequency of TDV perpetration are examined, as well as their associations with hypothesized precursors of TDV. Method: A sample of court-referred adolescents (n = 147, Mage = 15.85) completed a baseline assessment that included measures of three hypothesized precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Further, in using a cumulative incidence approach, we found higher rates of DV than even outlier (cross-sectional) studies using high-risk samples ( Alleyne-Green et al, 2012 ; Martin-Storey, 2015 ) and comprehensive measures ( Niolon et al, 2015 ). This pattern of results align with estimates derived from similar cumulative assessments over shorter timespans ( Jouriles et al, 2005 ; Krauss et al, 2020 ; Smith et al, 2003 ). Importantly, rates exceeded the field’s consensus on the prevalence for both sexual and physical DV in just three aggregated follow-ups, suggesting that future longitudinal research need not expend extensive resources to capture these numbers.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Further, in using a cumulative incidence approach, we found higher rates of DV than even outlier (cross-sectional) studies using high-risk samples ( Alleyne-Green et al, 2012 ; Martin-Storey, 2015 ) and comprehensive measures ( Niolon et al, 2015 ). This pattern of results align with estimates derived from similar cumulative assessments over shorter timespans ( Jouriles et al, 2005 ; Krauss et al, 2020 ; Smith et al, 2003 ). Importantly, rates exceeded the field’s consensus on the prevalence for both sexual and physical DV in just three aggregated follow-ups, suggesting that future longitudinal research need not expend extensive resources to capture these numbers.…”
Section: Discussionsupporting
confidence: 83%
“…These approaches risk underreporting of DV due to respondents forgetting or misremembering events (i.e., when asking about lifetime) or limiting their recall to short spans of time or limited partners. Alternatively, cumulative assessment approaches aggregate repeated measurements across (often shorter) reference periods rather than rely on a single-point retrospective report ( Caiozzo et al, 2016 ; Jouriles et al, 2005 ; Krauss et al, 2020 ). Since it is likely that reference period influences prevalence rates, a cumulative approach can mitigate some measurement error by capturing violence “missed” by lifetime lookbacks.…”
Section: Rates Of DV Perpetration and Victimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of more fined‐grained data limits our ability to understand how processes over hours, days or weeks influence the occurrence of dating violence episodes. Such data are needed to better understand how cognitions, motivating negative emotions, routine activities and adverse life‐events affect change and stability in coercive and aggressive episodes among dating partners (Krauss et al., 2020). Ecological momentary assessments may help to address this limitation (Shiffman et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these dimensions have had differing success in explaining offending, with differential association having the most empirical support and imitation having the least (Pratt et al, 2010). Previous meta-analyses have found that findings depend on crime type, demographics of sample, location, and research design (Kruis et al 2020; Pratt et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%